PENGARUH LATIHAN DI PASIR TERHADAP KECEPATAN TENDANGAN SABIT PADA ATLET PUTRA PERGURUAN KIJANG BERANTAI KOTA PONTIANAK - Ariska, Pika; Purnomo, Edi; Supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIn this study aims to determine the effect of training in the sand against the speed of the kick sickle on male athletes in the Pontianak City chain deer. And how much is the increase in training provided. This study was designed using an experimental method in the form of one group pre-test and post-test design. In this study, the number of research samples taken from the total population, namely 15 chain deer athletes. Data collection in this study may use a test technique with the type of test that is the speed of the sickle kick. Based on the results of data analysis, it was stated that there was an effect of training in sand on the speed of sickle kicks on male athletes in the Pontianak city chain deer. This was proven through calculations using SPSS version 22 ', obtained a sig count of 0,000 <0.05, then Ho was rejected, in other words sandy training had an effect on the speed of the sickle kick at a 95% confidence level, then the effect of training in the sand on the speed of the kick kick in male athletes experienced significant success, and experienced an increase in training given by 24.1%. Based on the categorization table the results of the final speed test for sickle kicks carried out by male martial arts athletes are categorized as "Good". And the results of the initial kick speed tests by male martial arts athletes are categorized as "sufficient". Keywords: Effect Of Exercise In Sand, Kick Scythe, Chain Deer, Pencak Silat.